Clinical and imaging services for TIA and minor stroke: results of two surveys of practice across the UK. Issue 8 (7th August 2013) - Brazzelli, Miriam; Shuler, Kirsten; Quayyum, Zahid; Hadley, Donald; Muir, Keith; McNamee, Paul; De Wilde, Janet; Dennis, Martin; Sandercock, Peter; Wardlaw, Joanna M
Abstract : Objectives: Transient ischaemic attack (TIA) is a medical emergency requiring rapid access to effective, organised, stroke prevention. There are about 90 000 TIAs per year in the UK. We assessed whether stroke-prevention services in the UK meet Government targets. Design: Cross-sectional survey. Setting: All UK clinical and imaging stroke-prevention services. Intervention: Electronic structured survey delivered over the web with automatic recording of responses into a database; reminders to non-respondents. The survey sought information on clinic frequency, staff, case-mix, details of brain and carotid artery imaging, medical and surgical treatments. Results: 114 stroke clinical and 146 imaging surveys were completed (both response rates 45%). Stroke-prevention services were available in most (97%) centres but only 31% operated 7 days/week. Half of the clinic referrals were TIA mimics, most patients (75%) were prescribed secondary prevention prior to clinic referral, and nurses performed the medical assessment in 28% of centres. CT was the most common and fastest first-line investigation; MR, used in 51% of centres, mostly after CT, was delayed up to 2 weeks in 26%; 51% of centres omitted blood-sensitive (GRE/T2*) MR sequences. Carotid imaging was with ultrasound in 95% of centres and 59% performed endarterectomy within 1 week of deciding to operate. Conclusions: Stroke-prevention services are widely available in the UK. Delays to MRI, its use in addition to CT while omitting key sequences to diagnose haemorrhage, limit the potential benefit of MRI in stroke prevention, but inflate costs. Assessing TIA mimics requires clinical neurology expertise yet nurses run 28% of clinics. Further improvements are still required for optimal stroke prevention.